Stem Of The Arts: Incorporating Art Into Stem Fields - Daniels, Robin N.; Duden, Rachael M.; Gunzelman, Kaylee Q. (My University, 2018)
Throughout this research project, we explored how arts can be intertwined into the STEM field. Collectively, we planned, created and facilitated three activities that centered around different styles of art-specifically the areas of art, music and dance. Our goal was to express to students how art and STEM can be used together and prove STEM is needed in areas of art. We conducted this research at Woodrow Wilson Elementary and various STEAM nights throughout the USD 383 school district. At the beginning of each activity, students were given a survey asking, “What is STEM?” and “Could art be a part of Stem?” Students recorded their responses before beginning the activities. The first activity we facilitated focused on incorporating art into STEM. Fourth-grade students were given the opportunity to let their imaginations run wild by using static electricity to make their creations come to life. Students were given a variety of materials (cardboard, tissue paper, markers and glue) to construct a “movable” project. After they finished, they were given balloons to explore how static electricity could make their art alive. The second activity we implemented centered around integrating music into STEM. Fifth-grade students used iPads to explore the Tynker App and create choreographed dances. Students activated their prior knowledge of coding to design a character and code it to create a dance. The third activity we conducted focused on incorporating music into STEM. Sixth-grade students were given a Makey Makey and asked to create a song utilizing their understanding of circuits. Using alligator clips, students were able to connect to a conductive material (bananas) and control their circuit boards. They were able to investigate how closed circuits worked in order to appropriately make the Makey Makey work. After each activity, we gave the students another short survey with the following two questions, “Could art be a part of STEM?” and “If so, how?” Before the activities, 80% of students stated that they could see art being a part of STEM. After facilitating each activity 90% of the students said they thought art was a part of STEM.